The director eaudiobook - Ignatius, David (Recorded Books Inc., 2014)
In David Ignatius' s gripping new novel, spies don' t bother to steal information . . . they change it, permanently and invisibly. Graham Weber has been director of the CIA for less than a week when a Swiss kid in a dirty T-shirt walks into the American consulate in Hamburg and says the agency has been hacked, and he has a list of agents' names to prove it. This is the moment a CIA director most dreads. Weber isn' t sure where to turn until he meets a charismatic (and unstable) young man named James Morris who runs the Internet Operations Center. He' s the CIA' s in-house geek. Weber launches Morris on a mole hunt unlike anything in spy fiction— one that takes the reader into the hacker underground of Europe and America and ends up in a landscape of paranoia and betrayal. Like the new world of cyber-espionage from which it' s drawn, The Director is a maze of deception and double-dealing— about a world where everything is written in zeroes and ones and nothing can be trusted.